The effects of compression garments on thermoregulatory response during exercise in the heat - Tsuji, B.; Watanabe, K.; Nishiyasu, T. (Advances in Exercise and Sports Physiology, 2013)
Purpose: This study examined the effects of wearing graduated compression tights (CG tights) on cutaneous vasodilatory and sweating responses to increasing core temperature during exercise in the heat. Methods: Subjects performed cycle exercise at 60% of peak oxygen uptake in the heat (30°C, 50% relative humidity) for 45 min. In this study, the effect of wearing CG tights (CG trial) was compared with that of wearing non-compression tights (Con trial). During the experiments, esophageal temperature (Tes), forearm vasclure conductance (FVC) and chest sweat rate were measured continuously. Results and Discussion: To estimate the relationship between core temperatur e and thermoregulatory responses, FVC and sweat rate were plotted against Tes. The Tes threshold for vasodilation did not differ between the two trials, but the sensitivity (the slope of Tes-FVC relation) and the peak value of FVC were significantl higher in the CG trial than in the Con trial. Sweating response to increasing core temperature did not differ significantly between the trials. These results suggest that wearing CG tights enhances cutaneous vasodilatory response to increasing core temperature during exercise in the heat.